Adopted Children and Their Relationship with Legacy : Perspectives of Ulama and KHI - sebyar, Muhamad Hasan (Jurnal Hukum Keluarga, 2024)
Raising children in Islam is mandatory, the right to care for children has a degree based on the benefit of the child. Starting from the mother and the immediate family of the mother, then the father's family according to the order of inheritance rights or the person given the mandate to maintain it. Today many children are cared for by non-biological parents, the problem is that most of them adopt equate children with biological children in terms of lineage, inheritance, mahram, and guardianship. This paper examines adopted children and their relationship with inheritance in Islamic law. The study employs an empirical juridist approach. The result of this research is that adopted children do not inherit assets from their adoptive parents, and vice versa. Adopted children can get the inheritance of their adoptive parents from the will or grant, and vice versa. The maximum amount of wills is 1/3 of the assets left if the deceased has an heir. If the deceased does not have an heir, it can be completely inherited.